Evolution of functional tissue engineering for tendon and ligament repair. (17th November 2022) - Butler, David L.
Abstract: This review paper is motivated by a Back‐to‐Basics presentation given by the author at the 2022 Orthopaedic Research Society meeting in Tampa, Florida. I was tasked with providing a brief history of research leading up to the introduction of functional tissue engineering (FTE) for tendon and ligament repair. Beginning in the 1970s, this timeline focused on two common orthopedic soft tissue problems, anterior cruciate ligament ruptures in the knee and supraspinatus tendon injuries in the shoulder. Historic changes in the field over the next 5 decades revealed a transformation from a focus more on mechanics (called "bioMECHANICS") on a larger (tissue) scale to a more recent focus on biology (called "mechanoBIOLOGY") on a smaller (cellular and molecular) scale. Early studies by surgeons and engineers revealed the importance of testing conditions for ligaments and tendons (e.g., high strain rates while avoiding subject disuse and immobility) and the need to measure in vivo forces in these tissues. But any true tissue engineering and regeneration in these early decades was limited more to the use of auto‐, allo‐ and xenografts than actual generation of stimulated cell‐scaffold constructs in culture. It was only after the discovery of tissue engineering in 1988 and the recognition of frequent rotator cuff injuries in the early 1990s, that biologists joined surgeons and engineers to discover mechanical and biological testing criteria for FTE. This review emphasizes the need for broader and more inclusive collaborations by surgeons, biologists and engineers in the short term with involvement of those in biomaterials, manufacturing, and regulation of new products in the longer term.